(2x-3) ( x ² -1 )- ( x +1)(3x-7)

(2x-3) ( x ² -1 )- ( x +1)(3x-7)

2 bình luận về “(2x-3) ( x ² -1 )- ( x +1)(3x-7)”

  1. Giải đáp:
    2x^{3}-6x^{2}+2x+10
    Lời giải và giải thích chi tiết:
     (2x-3).(x^{2}-1)-(x+1).(3x-7)
    =[2x.(x^{2}-1)-3.(x^{2}-1)]-[x.(3x-7)+1.(3x-7)]
    =2x^{3}-2x-3x^{2}+3-(3x^{2}-7x+3x-7)
    =2x^{3}-2x-3x^{2}+3-3x^{2}+4x+7
    =2x^{3}-(3x^{2}+3x^{2})+(4x-2x)+(3+7)
    =2x^{3}-6x^{2}+2x+10

    Trả lời
  2. Giải đáp + Lời giải và giải thích chi tiết:
    (2x – 3)(x^2 – 1) – (x + 1)(3x – 7)
    = 2x × x^2 – 2x × 1 – 3 × x^2 – (-3) × 1 – x × 3x – x × 7 – 1 × 3x – 1 × 7
    = 2x^3 – 2x – 3x^2 + 3 – 3x^2 – 7x + 3x – 7
    = 2x^3 – 2x – 7x – 3x – 3x^2 – 3x^2 + 3 – 7
    = 2x^3 – 12x – 6x^2 – 5

    Trả lời

Viết một bình luận

Câu hỏi mới